Concise dermatology - Das, Amupam; Sethi, Sumit; Sarkar, Rashmi (Boca Raton, FL : CRC Press, 2021)
This concise text from an internationally respected editor presents the most important points about the most important topics in disease of the skin, hair, and nails; any medical professional will find here the material for a solid grounding in the subject.
Includes index.
Keywords: Skin Manifestations; Handbook; Skin Diseases